Theophrastus of Eresus : sources for his life, writings, thought and influence. - Theophrastus.; Fortenbaugh, William W.; Gutas, Dimitri.; Huby, Pamela M.; Sharples, R. W. (Philosophia antiqua,, 1995)
This volume forms part of the international Theophrastus project started by Brill in 1992 and edited by W.W. Fortenbaugh, P.M. Huby, R.W. Sharples and D. Gutas. Along with volumes containing texts and translations, the commentary volumes provide classicists and philosophers with an up-to-date collection of the material relating to Theophrastus (ca. 370-286 BC), Aristotle's pupil and successor as head of the Peripatetic school. This is the second volume of Huby's commentary on Theophrastus of Eresus. Sources for His Life, Writings, Thought and Influence . Dimitri Gutas has written on the Arabic passages, including some unique material, and Pamela Huby has covered the rest. Theophrastus largely followed Aristotle's logical views, but made important changes in modal logic, and dealt with hypothetical and prosleptic syllogisms. He also influenced medieval logic.